Development of an evidence-based complementary feeding practice module for mothers using the combined Delphi Method - Rini Andriani; Damayanti Rusli Sjarif; Bambang Supriyatno; Aria Kekalih; Hartono Gunardi; Ika Karlina Idris (Paediatrica Indonesiana, 2022)
Background Malnutrition in infants remains a challenge in Indonesia. Malnutrition often arises as a result of errors in complementary feeding practices. An education module for Indonesian mothers may help them correctly implement complementary feeding practices. Objective To develop a module on correct complementary feeding practices for infants aged 6-9 months that can be read and understood by Indonesian mothers. Methods We performed qualitative research using the two-round Delphi method combined with group discussions. The first round listed the most important sub-themes of the module, while the second round sought approval for the module from experts. The Delphi team members were included using purposive and snowball sampling methods. Expert opinions were summarized and rearranged using the Steps for Coding and Theorization (SCAT) method. Results Ten experts were included in the Delphi team, with a mean duration of work experience of 28.5 (SD 12.37) years. The correct practices for giving complementary foods according to scientific evidence was named the ABC-Makanan PendampingASI/MPASI-Press (“Printed ABC of Complementary Feeding”) module and was summarized into four main topics: timely, adequate, safe, and responsive feeding. This module was made using language, photos, and images that were easily understood by mothers and included the suitable nutritional compositions to meet the needs of infants aged 6-9 months. Conclusion We developed the ABC-MPASI-Press module based on scientific evidence and experts’ reviews using the combined Delphi method. This educational guide is expected to inform mothers about correct complementary feeding practices for infants aged 6-9 months in order to prevent malnutrition.